1989
DOI: 10.1029/jb094ib06p07129
|View full text |Cite
|
Sign up to set email alerts
|

Appalachian Stress Study: 1. A detailed description of in situ stress variations in Devonian shales of the Appalachian Plateau

Abstract: We describe an experiment to measure variations in the state of stress within a horizontally bedded Devonian shale/sandstone/limestone sequence in western New York. A total of 75 stress measurements were made in three wells a kilometer or so apart using a wireline‐supported hydraulic‐fracturing system. The stress profiles indicate that a major drop in horizontal stress level occurs in the generally massive shales. This drop occurs principally across the lowermost member of a group of sand beds and corresponds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 29 publications
7
45
0
2
Order By: Relevance
“…This particular dataset might be regarded as problematic given that the vertical stress values are much larger than expected from the loading effect of the overburden; however, in this formerly glaciated region, the possibility exists that the vertical stress has not re-equilibrated following removal of the former ice load (cf. Evans et al, 1982Evans et al, , 1989. Furthermore, the E-W orientation of the maximum principal stress determined in modern measurements is consistent with the design of this mine (Bauer et al, 2005), indicating that the mining activity has not perturbed the orientation of the stress field.…”
Section: Figure 6 Here: Mohr Circle Diagramsupporting
confidence: 54%
See 2 more Smart Citations
“…This particular dataset might be regarded as problematic given that the vertical stress values are much larger than expected from the loading effect of the overburden; however, in this formerly glaciated region, the possibility exists that the vertical stress has not re-equilibrated following removal of the former ice load (cf. Evans et al, 1982Evans et al, , 1989. Furthermore, the E-W orientation of the maximum principal stress determined in modern measurements is consistent with the design of this mine (Bauer et al, 2005), indicating that the mining activity has not perturbed the orientation of the stress field.…”
Section: Figure 6 Here: Mohr Circle Diagramsupporting
confidence: 54%
“…The layered stratigraphy ( Fig. 2(a) presents a further complicating factor, it having long been recognized both observationally and via numerical modelling (e.g., Evans et al, 1989;Warpinski, 1989;Brenner and Gudmundsson, 2004) (2014) reported is ~7500 psi which corresponds to ~52 MPa; if this point were not mentioned, readers might be puzzled as to the mismatch between the earlier statements that the BHP is subject to considerable uncertainty and the portrayal of precise values for this parameter by Clarke et al (2014).…”
Section: Stress Perturbation Due To Pressure Of Fracking Fluidmentioning
confidence: 87%
See 1 more Smart Citation
“…These values were selected to simulate remote stresses 15% higher in the shale interlayer than in the adjacent siltstones. This is a reasonable stress ratio based on estimates of in-situ stress in layered rock (Evans et al, 1989). An applied strain of 1 £ 10 23 results in a theoretical crack-normal stress (s xx r ) of 16.5 MPa in the siltstones and 19 MPa in the shale layer.…”
Section: Coupling Through a Shale Interfacementioning
confidence: 99%
“…If bypass did occur, however, the slow pressure decays following shut-in and the similarity of these shut-in decay curves between cycles ( Figure A1) suggest that the resulting leak rates are small. In this regard, Evans et al [1988b] describe a number of hydraulic fracturing tests in shale for which'packer bypass was indicated and note that this did not appear to have a significant effect upon the determined ISIPs.…”
Section: Discussionmentioning
confidence: 99%